Second Chance Hero - Wilde, Lori (New York : Forever, Hachette Book Group, 2019)
Wedding videographer Tish Gallagher is at the end of her rope. Shes just spent her last buck on nonreturnable (but oh so fabulous) shoes. And her most sustainable relationship is with a pint of ~Hagen-Dazs. So she makes a wish on a lucky wedding veil...and sees the man she never stopped loving, her ex-husband, secret service agent Shane Tremont. Sure, their chemistry was hotter than a Texas summer, but their clashes were legendary, and no amount of longing will change that. When her dream job of recording the first daughters wedding appears out of the blue, Tish knows its her only shot to get out of the red. Just one teensy glitch: Shane is the groom. From the moment they see each other, she knows nothings changed--the same old magic is still between them, as irresistible and potent as ever. But hes promised to another and Tish has been burned before.
Keywords: Divorced people -- Fiction; Weddings -- Fiction; Love stories